Application of an alternative analysis model ANCOVA on Eucalyptus based agroforestry experiments in red and lateritic zone in West Bengal - Saha, Abhijit; Roy, Moupiya; Majumder, Anurup; Basak, Jit Sankar; Middya, Md. M.H. (Indian Journal of Agroforestry, 2021)
Analysis of covariance (ANCOVA) model has been applied on Eucalyptus based agroforestry system for consecutive two years (2012 and 2013) at Regional Research Station of BCKV, Jhargram, West Bengal. Traditional analysis of variance (ANOVA) model has been applied and efficiency values of two analysis models were compared. Firstly, the covariates were selected by application of homogeneity of regression slope (HOS) methods. The selected covariates were soil pH, organic carbon (OC), available nitrogen (kg ha-1) and available potash (kg ha-1). Among them, available nitrogen has performed better as covariate for both the years (2012 and 2013) and the relative efficiency of ANCOVA over ANOVA model were 190.279 and 196.691, respectively for 2012 and 2013.